PIROLISIS LAMBAT SPIRULINA PLATENSIS PADA SUHU 400˚C - Nela Gamboa Rodriques; R.R Dirgarini Julia Nurlianti Subagyono; Abdul Aziz (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2025)
This study aims to investigate the slow pyrolysis of Spirulina platensis using a laboratory-scale reactor. The slow pyrolysis was conducted at 400°C for 60 minutes. The results showed that the bio-oil yield obtained was 9%. Gas Chromatography-Mass Spectrometry (GC-MS) analysis revealed that the dominant compounds in the bio-oil were hexadecanoic acid, N-Tetradecanoic Acid Amide, 1H-Indole and Phenol,4-Methyl, which are degradation products of lipids and proteins. Keywords: Spirulina platensis, slow pyrolysis, bio-oil, temperature, chemical composition